Modification of Cellulose Nanocrystals With 2-Carboxyethyl Acrylate in the Presence of Epoxy Resin for Enhancing its Adhesive Properties - Ali, Amjad; Aziz, Tariq; Zheng, Jieyuan; Hong, Fan; Awad, Mahamed F.; Manan, Sehrish; Haq, Fazal; Ullah, Asmat; Shah, Muhammad Naeem; Javed, Qaiser; Kubar, Ameer Ali; Guo, Li (Frontiers in Bioengineering and Biotechnology, 2022)
Cellulose nanocrystals (CNCs) have unparalleled advantages in the preparation of nanocomposites for various applications. However, a major challenge associated with CNCs in nanocomposite preparation is the lack of compatibility with hydrophobic polymers. The hydrophobic modification of CNCs has attracted increasing interest in the modern era standing with long challenges and being environmentally friendly. Here, we synthesized CNCs by using cotton as raw material and then modified them with 2-carboxyethyl acrylate to improve their corresponding mechanical, adhesive, contact angle, and thermal properties. Different concentrations (1-5 wt.%) of CNCs were used as modifiers to improve the interfacial adhesion between the reinforced CNCs and E-51 (Bisphenol A diglycidyl ether) epoxy resin system. CNCs offered a better modulus of elasticity, a lower coefficient of energy, and thermal expansion. Compared with the standard sample, the modified CNCs (MCNCs) showed high shear stress, high toughness, efficient degradation, thermal stability, and recycling due to the combined effect of the hyperbranched topological structure of epoxy with good compatibility. The native CNCs lost their hydrophilicity after modification with epoxy, and MCNCs showed good hydrophobic behavior (CA=105 ± 2°). The findings of this study indicate that modification of CNCs with 2-carboxyethyl acrylate in the presence of epoxy resin and the enhancement of the features would further expand their applications to different sectors.